Corynopuntia halophila (Cactaceae), a new species from Coahuila, Mexico. (4th May 2018) - Donati, Davide
Abstract: A new halophilous–gypsicolous species of Corynopuntia, C. halophila (Cactaceae), is described and illustrated from the state of Coahuila, north-eastern Mexico. It is morphologically similar to the diploid Corynopuntia moelleri, but it differs by some traits, such as body size and some unusual morphological features which are here reported for the first time; there are also ecological and karyological differences, as the latter study revealed that C. halophila is a polyploid with 2 n = 44 chromosomes. Diagnostic morphological characters from similar taxa are discussed and arranged in a taxonomic key. Knowledge of the species ecology, biogeography, demography and conservation status is also provided.